In Vitro Activities of Ceftobiprole and Doripenem Tested against Frequently Encountered Aerobic and Facultative Gram-Positive and Gram-Negative Bacterial Pathogens Isolated from Patients in Canadian Hospitals in 2007 - James A Karlowsky; Mel DeCorby; Daryl J Hoban; George G Zhanel (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In 2008, ceftobiprole was approved by Health Canada for the treatment of patients with complicated skin and skin structure infections including diabetic foot infections; approval of ceftobiprole by the United States Food and Drug Administration is pending. Doripenem is currently under review by Health Canada and was approved by the United States Food and Drug Administration in 2007 for the treatment of patients with complicated intra-abdominal infections and complicated urinary tract infections, including pyelonephritis. OBJECTIVES: To determine the in vitro activities of ceftobiprole and doripenem using a collection of frequently isolated aerobic and facultative bacteria cultured from patient blood, urine, respiratory and wound specimens in 12 Canadian hospitals in 2007. MEtHODS: Isolates were tested for their susceptibility to a panel of antimicrobial agents using the Clinical and Laboratory Standards Institute broth microdilution method. RESULTS: Ceftobiprole inhibited all isolates of methicillin-resistant Staphylococcus aureus (n=385), methicillin-resistant Staphylococcus epidermidis (n=20), methicillin-susceptible S aureus (n=1095) and methicillin-susceptible S epidermidis (n=108) at a minimum inhibitory concentration (MIC) of 2 μg/mL or less; all isolates of Streptococcus pyogenes (n=105) were inhibited by ceftobiprole at 0.06 μg/mL or less. All isolates of S aureus (MIC 4 μg/mL or less) and S pyogenes (MIC 0.5 μg/mL or less) tested were susceptible to ceftobiprole. Greater than 99% of extended-spectrum beta-lactamase (ESBL)-negative Escherichia coli (n=1528) and Klebsiella pneumoniae (n=436) were susceptible to ceftobiprole (MIC 1 μg/mL or less); against other genera/species of Enterobacteriaceae, susceptibility to ceftobiprole ranged from 80.7% for Enterobacter cloacae (n=166) to 99.2% for Proteus mirabilis (n=119). Ceftobiprole was less active against Pseudomonas aeruginosa (n=633) (90% of isolates inhibited at a concentration of 32 μg/mL [MIC90]) than Enterobacteriaceae. Doripenem inhibited 90% of isolates of E coli (n=1577) and K pneumoniae (n=456), including ESBL-producing isolates (n=69), and E cloacae at a concentration of 0.06 μg/mL or less; doripenem and meropenem had MIC90s of 8 μg/mL for the isolates of P aeruginosa tested. Doripenem demonstrated in vitro activity indistinguishable from that of meropenem against Gram-positive pathogens. CONCLUSIONS: All isolates of methicillin-resistant S aureus tested were susceptible to ceftobiprole (MIC 4 μg/mL or less), differentiating it from any other currently marketed beta-lactam. Doripenem demonstrated potent activity (MIC90 0.5 μg/mL or less) against all isolates of Enterobacteriaceae tested, including ESBL-producing E coli and K pneumoniae, and as potent activity as meropenem (MIC90 8 μg/mL) against P aeruginosa. The current study demonstrated both ceftobiprole and doripenem to be promising broad-spectrum antibacterial agents.